Heteronormativity in secondary schools in Zagreb - Bijelić, Nataša (Družboslovne razprave, 2013)
This paper analyses the presence and characteristics of heteronormativity in the context of the Croatian school system by focusing on secondary schools in the capital of Zagreb. We base our analysis on the results of a survey on opinions and attitudes regarding homosexuality conducted on a sample of 322 students and 117 teachers in nine secondary schools. The research reveals that stereotypes and prejudice towards lesbians and gays are omnipresent and widespread. Both students and teachers hold highly discriminatory attitudes concerning the visible/public expression of non-heteronormative gender and sexual identities. In addition, almost one-third of all students reported having resorted to verbal/physical violence against a person because of their alleged homosexual orientation. Moreover, we explore the research findings in relation to the (non)existence and (in)visibility of LGBT issues in school curricula and textbooks. In addition, we consider the recent (September 2012) introduction of a Health Education curriculum which for the first time introduces into Croatian schooling the topics of 'acceptance of sexual diversity' and 'stigmatisation and discrimination of sexual minorities'. Finally, we outline public debates and reactions to this 'introduction of homosexuality to Croatian schools' coming from the Croatian Catholic Church and faith-based organisations.
Keywords: Homoseksualnost; Homosexuality; Stereotipi; Stereotypes; Sex education; Spolna vzgoja; Srednje šole; High schools; Croatia; Hrvaška